The dialectic of love and the motif of fruit in Hegel's Phenomenology of Spirit. Issue 1 (2nd January 2017) - Phipps, Gregory
ABSTRACT: Some of the more radical scholarship in contemporary Hegelian studies centres on the idea that Hegel is a 'philosopher of love'. But to what extent does a Hegelian understanding of love capture the dialectical movement towards Absolute Knowing? This article addresses this question through an analysis of the motif of fruit in Phenomenology of Spirit. In the first part of the article I examine how scholars such as Slavoj Žižek locate sensual and erotic overtones in the movement of the dialectic. I argue that these approaches offer largely metaphoric readings of contradiction, duality, and the Absolute. In the second part of the article I argue that Hegel himself develops metaphors for these concepts in the Phenomenology, most notably through the motif of fruit. This motif brings out a contrast between a scientific conception of the Absolute and the erotic, contingent, and 'feminine' aspects of love. Significantly, the fruit begins as an image of wholeness and unity and ends as an image of unrestrained sensuousness. In this way, the motif evolves within the formal structure of the dialectic, forming an increasingly stark opposition to Absolute Knowing.